Length–weight relationships of four small indigenous freshwater fishes from the subtropical Ganga River, India. Issue 4 (20th October 2020) - Alam, Absar; Jha, Dharm Nath; Verma, Sushil Kumar; Verma, Hari Om; Mishra, Sandeep Kumar; Das, Shyamal Chandra Sukla; Kumar, Jeetendra; Thakur, Venkatesh RamaRao; Gupta, Monika; Das, Basanta Kumar
Abstract: Basic information on length–weight relationships for a number of small indigenous tropical freshwater fish species is still sparse or not available on the FishBase. The p resent study reports the weight–length relationships of four species from the Ganga River in India. A total of 795 fresh fish specimens of Pethia gelius, Corica soborna, Parambassis baculis and Aborichthys elongatus were collected from four different locations along stretches of the Ganga River from June 2017 to August 2018. The r 2 and b values for the four fish species ranged from 0.949 to 0.998 and 2.55 to 2.849, respectively. Length–weight relationships for P. gelius, P. baculis and A. elongatus represent the first information from the Ganga River. A new record for the maximum size of C. soborna was documented as 8.54 cm TL and 4.25 g.